2018
DOI: 10.3390/geriatrics4010006
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Stigma Among Healthcare Staff

Abstract: Older people with delirium occupy more than one third of acute medical beds and require increased medical attention, as care at present is suboptimal. In addition, since delirium is undetected, it should form a target for teaching in wards. Moreover, as people with delirium are largely dependent on daily interactions and care by inpatients professional staff, it is important to address stigmatisation of these vulnerable patients. This is especially important as previous studies have shown that negative staff a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, educational and experience-related aspects did not play an important role with regard to stigmatization. 52 By contrast, in a more recent study, Mossello et al (2020) 53 suggested that health personnel ′ s education can improve their attitudes toward delirium patients and increase awareness of the condition.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, educational and experience-related aspects did not play an important role with regard to stigmatization. 52 By contrast, in a more recent study, Mossello et al (2020) 53 suggested that health personnel ′ s education can improve their attitudes toward delirium patients and increase awareness of the condition.…”
Section: Discussionmentioning
confidence: 96%
“…Mukaetova-Ladinska et al . (2019) 52 found that professionals who worked closely with patients with delirium attained the destigmatization of these patients. However, educational and experience-related aspects did not play an important role with regard to stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that students gained more insight into what a delirious patient endures during delirious episodes; however, in actual practice, understanding of the patient’s needs is often lacking [ 6 , 7 ]. It would be interesting and relevant to study if and how students and health care professionals who work with delirious patients change their behaviors and attitudes when they encounter delirious patients in real life, after playing the game, particularly since destigmatization seems to occur when working closely with delirious patients who use to be stigmatized [ 35 ].…”
Section: Discussionmentioning
confidence: 99%